NAČELA ODREĐIVANJA SINONIMA (Filološke pripombe, 2019)
The article discusses differences in approaches to synonymes. Various classifications (two, three or more groups), terminology (e.g. total, complete, absolute, partial, descriptive,  propositional, near-synonymy) and definitions are briefly analysed, mainly on Croatian examples.Cognitive prototypical theory is applied to different criteria used in most approaches to synonymes up to now. It is shown that differences in forms of synonymes, as well as meaning differences, may exibit various levels and shapes which contribute to the overall synonymic status of a pair or group in terms of prototypicaliti or marginality. It seems that (almost) any type of synonymic relations described in literature so far may be included in the concept of synonymes, but with different relationship to the focal members.